Comparison of AngularJS and VueJS frameworks efficiency - Naгar Patrylo (Journal of Computer Sciences Institute, 2017)
The article presents the results of a comparative analysis of JavaScript AngularJS and VueJS frameworks to create user interfaces. The study of productivity has been achieved through the implementation of JavaScript applications using both frameworks. Each of them was executed and the performance was measured. The results was a basis is the analysis. The analysis was done using the code build in the applications as well as the developer tools of web browsers.